Infertility Patients Related To Menarche Age and Nutritional Status at Halim Fertility Center Clinic Medan - Tambun, Mastaida (Asian Journal of Pharmaceutical Research and Development, 2022)
Objective: This study aims to determine the relationship between Menarche Age and Nutritional Status on infertility patients. Infertility is one of the reproductive health problems that have not been completely resolved. Infertility is defined as the inability to have children or a condition where a married couple has not been able to have children even though they have had sexual intercourse 2-3 times a week for a period of 1 year without using contraception. Infertility affects the psychology of married couples so that it triggers marital problems such as divorce, and relationships that are not harmonious. Methods: The research method used is quantitative analytic with a case control approach. Case control approach is a research that studies the influence of risk factors (independent) and effect factors (dependent), at the same time. The study was conducted at the Halim Fertility Center/HFC Clinic with the study population consisting of Couples of Childbearing Age (EFA) with the number of samples (Cases and Controls) taken proportionally 1:1, 40 Cases: 40 Controls, so the total sample size was 80 samples. Results: The results of the bivariate analysis between the age of menarche and the incidence of infertility, statistically the Odds Ratio value was 3.85 (95% CI; 1.38-10.764), meaning that respondents with abnormal menarche age had a 3.85 times greater risk of experiencing infertility compared to respondents who have normal age of menarche. With p-value = 0.016, it means that there is a significant relationship between the age of menarche and the incidence of infertility. It can be concluded that the abnormal age of menarche is a risk factor for infertility. The results of the bivariate analysis between nutritional status and the incidence of infertility statistically obtained the Odds Ratio value of 4.846 (95% CI; 1.43-16.42) meaning that respondents who were obese had a 4.846 times greater risk of experiencing infertility compared to those who were not obese. . With p-value = 0.016, it means that there is a significant relationship between nutritional status and the incidence of infertility. It can be concluded that nutritional status is a risk factor for infertility. The results of the independent variables (age of menarche, and nutritional status) met the candidate requirements for inclusion in the multivariate test. Conclusion: The factors of age at menarche and nutritional status have a risk for the incidence of infertility in couples of childbearing age at the Halim Fertility Center Clinic in Medan. It can be concluded that the age of menarche and nutritional status have a significant relationship with the incidence of infertility.